2006
DOI: 10.1007/s00262-006-0237-4
|View full text |Cite
|
Sign up to set email alerts
|

In the FVB/N HER-2/neu transgenic mouse both peripheral and central tolerance limit the immune response targeting HER-2/neu induced by Listeria monocytogenes-based vaccines

Abstract: Listeria monocytogenes-based vaccines for HER-2/neu are capable of breaking tolerance in FVB/N rat HER-2/neu transgenic mice. The growth of implanted NT-2 tumors, derived from a spontaneously occurring tumor in the FVB/N HER-2/neu transgenic mouse, was significantly slower in these mice following vaccination with a series of L. monocytogenes-based vaccines for HER-2/neu. Mechanisms of T cell tolerance that exist in these transgenic mice include the absence of functional high avidity anti-HER-2/neu CD8(+) T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 44 publications
1
45
2
Order By: Relevance
“…We have described Listeria monocytogenes-based vaccines expressing overlapping fragments of HER-2/neu that are equally capable of inducing stasis in the growth of transplanted tumors in wild-type FVB/N mice (9) and HER-2/neu transgenic mice (10). We now show that these vaccines differ in delaying the onset of autochthonous tumor growth in transgenic mice.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have described Listeria monocytogenes-based vaccines expressing overlapping fragments of HER-2/neu that are equally capable of inducing stasis in the growth of transplanted tumors in wild-type FVB/N mice (9) and HER-2/neu transgenic mice (10). We now show that these vaccines differ in delaying the onset of autochthonous tumor growth in transgenic mice.…”
Section: Introductionmentioning
confidence: 94%
“…The 3T3 cell line is a mouse fibroblast line that expresses MHC class I molecules of the ''q'' haplotype. The propagation of NT-2 and 3T3 cells has been previously described in detail (10)(11)(12) used in a standard CTL assay with 3T3 target cells loaded with 1 Ag/mL of the target peptide as described previously (10,12).…”
Section: Methodsmentioning
confidence: 99%
“…Also, vaccination with Listeria vaccines expressing fragments of Her2/neu, fused to LLO, were effective against primary tumors in a syngeneic mouse breast tumor model, NT-2, expressing Her2/neu, which correlated with strong immune responses to Her2/neu. 54 These vaccines were also effective against NT-2 when implanted into a syngeneic HER-2/neu transgenic mouse, 55 which displays profound tolerance to HER-2/neu. Female HER-2/neu transgenic mice develop mammary tumors by about 5-9 mo of age but the HER-2/neu expressing Listeria vaccines delayed the appearance of mammary tumors in these mice.…”
mentioning
confidence: 99%
“…60,[63][64][65] Using transgenic mouse models of cancer, L. monocytogenes based vaccines have been shown to have an ability to overcome tolerance mechanisms and mount an efficient immune response towards the tumors. 66,67 These studies have also shown that Listeria-based vaccines can impact on both central and peripheral tolerance mechanisms. In addition, it has been demonstrated that an immune response to overcome these tolerance mechanisms can have a therapeutic effect on the growth of both transplanted and spontaneous tumors in these models.…”
Section: Phase I Clinical Studiesmentioning
confidence: 99%
“…In addition, it has been demonstrated that an immune response to overcome these tolerance mechanisms can have a therapeutic effect on the growth of both transplanted and spontaneous tumors in these models. 66,67 The ability to overcome tolerance in these mouse models is an important aspect of these therapies as treatments that are effective in animals tolerant to the tumor antigen will theoretically have a greater chance of being effective in human clinical trials.…”
Section: Phase I Clinical Studiesmentioning
confidence: 99%